Ekologian, ympäristön ja sukupuolen vaikutus sympatristen kolmipiikkiekotyyppien loisyhteisöihin Islannissa - Lanki, Maiju (Helsingfors universitet, 2013)
Adaptive radiation is an important mechanism of evolution, which can lead to emergence of sympatric species or morphotypes. Among other biological interactions, parasitic pressure can have significant evolutionary implications for host populations by reducing the fitness of the host individuals. Parasite community structure of fishes is typically strongly dependent on both host ecology (e.g. habitat and feeding behaviour) and environmental factors (e.g. water quality and temperature). However, the relative importance of these factors for parasite-mediated speciation is not known. Also, host gender-specific differences in parasite communities can have an effect on the differentiation of host morphs. In this Master's thesis, I focused on differences in parasite communities of sympatric morphs of three-spine stickleback (Gasterosteus aculeatus) in two large Icelandic lakes, Thingvallavatn and Mývatn. In these lakes, the habitats of sympatric mud and lava morphs are the same (soft/hard bottom), but the habitat water temperatures are opposite between the lakes. In this unique system, it is thus possible to compare between the effects of host ecology and water temperature on parasite community structure and strength of parasite-mediated selection. Additionally, I studied the effect of host sex on the parasitic pressure. There is also a third stickleback morph, Nitella morph, inhabiting the cold limnetic habitats in Lake Thingvallavatn. I sampled the stickleback morphs from both lakes and identified their parasite species. I discovered a total of five parasite genera: trematodes Apatemon and Diplostomum, and cestodes Diphyllobothrium, Proteocephalus and Schistocephalus. Most of the observed parasites have negative effects on health and fitness of the host. I found more parasites in sticklebacks living in higher temperature in both lakes regardless of the morph. When comparing the cold water morphs in Thingvallavatn, parasite abundance was higher in the limnetic Nitella morph than in the shallow water lava morph. Fish ...